Togo : 2002 Article IV Consultation and Review of the Staff-Monitored Program-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2003)
Togo's macroeconomic situation remained difficult owing to its political uncertainty, falling cotton prices, and continued problems in phosphate production under the Staff-Monitored Program. Executive Directors stressed the need to improve fiscal stance, address structural issues, and reinforce the role of cotton producers. They urged the authorities to press ahead with efforts to improve the compilation of economic and social statistics, and considered that Togo's participation in the General Data Dissemination System would help establish a framework for broad-based improvements in the country's statistical systems.